Elaboración y aplicación de una guía didáctica de técnicas grafo plásticas con material reciclable, para mejorar el aprendizaje, en la ludoteca de la carrera de educación parvularia de la universidad técnica de Cotopaxi en el sector Eloy Alfaro del cantón Latacunga, provincia de Cotopaxi durante el período 2011-2012 - Jácome Arequipa, Ana Veronica (2014)
The Ludoteca aims to acquire children learning through play, the kindergarten teachers as inspiring and innovative activities executed, making creative children, happy and spontaneous, opening doors to the world of fantasy that leads to the integral formation of the deponent, where there is bidirectional communication that is the exchange of ideas meaningful and lasting. This research was based on technical activities with recyclable plastic graph in order to improve learning this will allow children to function in activities with safety and confidence, strengthening fine motor skills, expressing their emotion sand concerns, developing latent abilities this concept will be felt on every work of art that expresses the educational community in a creative, learning to care for the environment and raise awareness of importance of recycling.